PENINGKATAN MOTIVASI DAN HASIL BELAJAR DENGAN MEDIA â€œAKSELERASI INDONESIAâ€ - Huda, Nur Kholis (Institut Agama Islam Syarifuddin Lumajang, 2018)
The students? low interest in learning Social science, especiallyon the changes of provinces in Indonesia, has an impact on their learning motivation which automatically makes the studying outcomes are not satisfying. This is experienced by class VI students of Jetis III Elementary school during 2016/2017 period. This article observes about the methods to increase learning motivation and student learning outcomes in Social Science particularly about the changes of Provinces in Indonesia by using media learning called